2011
DOI: 10.1167/iovs.11-8312
|View full text |Cite
|
Sign up to set email alerts
|

p53-Regulated Increase in Oxidative-Stress–Induced Apoptosis in Fuchs Endothelial Corneal Dystrophy: A Native Tissue Model

Abstract: FECD CECs are more susceptible to oxidative DNA damage and oxidative-stress-induced apoptosis than normal. Increased activation of p53 in FECD suggests that it mediates cell death in susceptible CECs. The authors conclude that p53 plays a critical role in complex mechanisms regulating oxidative-stress-induced apoptosis in FECD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 14 publications
3
91
0
1
Order By: Relevance
“…When MN is neutralized by 2-electron reduction by NAD(P)H quinone dehydrogenase 1 (NQO1), it forms a stable hydroquinone without abnormal ROS generation. In FECD, there is decrease in Nrf2-dependent antioxidant defense shown by decreased nuclear Nrf2 translocation and the ability to upregulate antioxidant response element-dependent antioxidants, such as NQO1 (2). Due to the deficient 2-electron reductive scavenging by NQO1, it is envisaged that MN is reduced by the 1-electron pathway, causing greater internal ROS production and overwhelming the antioxidant system that is dysfunctional in FECD (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When MN is neutralized by 2-electron reduction by NAD(P)H quinone dehydrogenase 1 (NQO1), it forms a stable hydroquinone without abnormal ROS generation. In FECD, there is decrease in Nrf2-dependent antioxidant defense shown by decreased nuclear Nrf2 translocation and the ability to upregulate antioxidant response element-dependent antioxidants, such as NQO1 (2). Due to the deficient 2-electron reductive scavenging by NQO1, it is envisaged that MN is reduced by the 1-electron pathway, causing greater internal ROS production and overwhelming the antioxidant system that is dysfunctional in FECD (35).…”
Section: Discussionmentioning
confidence: 99%
“…Cell loss in FECD has been shown to be mediated by apoptosis and specifically p53 (2,6,23). Next, we investigated whether caspase activation was involved in rosette formation, leading to endothelial cell loss.…”
Section: Mn-induced Apoptosis Is Caspase Dependent During Rosette Formentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress and apoptosis are reported to play a role in the development of FECD particularly in regard to accelerated corneal endothelial cell loss (Borderie et al 2000;Li et al 2001;Buddi et al 2002;Szentmáry et al 2005;Engler et al 2010;Jurkunas et al 2010;Azizi et al 2011). This may be in part due to chronic ultraviolet (UV) light exposure (Inoki et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…44 Interestingly, several authors have found evidence of increased apoptosis having a role in endothelial cell loss, as observed in FECD. 46,47 Furthermore, it was shown that the defense mechanism of FECD endothelium against oxidative stress-induced damage is impaired when compared with normal cells, 39,45,48,49 which is supported by the observed significant higher levels of (baseline) oxidative stressinduced damage, 43,45,48 and changes in endothelial cell morphology characteristic for oxidative stress. 50 These data suggest that chronic oxidative stress contributes to the pathophysiology of FECD, and that the decreased defense system renders FECD endothelial cells even more susceptible to oxidative stress-induced damage than normal cells already are.…”
Section: Pathophysiology Of Fecdmentioning
confidence: 90%